(3PcQ GdCbQGf hQhGjGJge Yf HYVge HYVkGs - (3YHO Gddg Hf eMeO Hf LYaQ Hf MHGf GdCUHgGfj GdMHGfj , CHh eMeO,J (B369 (3g` s
(3ChdgG (B:s
(3Chdg HYO GdHSedI (B: (3GdMeO ddg Mb MeOg PcQ cd ef Qhi Yf QLd Ke Qhi Pdc GdQLd Yfg ef GdJGHYjf hZjQge s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B120 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B114s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B67 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs